2018
DOI: 10.3390/su10093239
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Assessment of Comprehensive Ecological Risk for a Loess Erosion Gully: A Case Study of Dujiashi Gully, Northern Shaanxi Province, China

Abstract: As a tool that can effectively support ecosystem management, ecological risk assessment is closely related to the sustainable development of ecosystems and human well-being and has become an active area of research in ecology, geography and other disciplines. Taking Dujiashi Gully for the study of gully loess erosion, a comprehensive risk assessment system for identifying risk probability, sensitivity and impairment was established. The spatial distribution of comprehensive ecological risk was analyzed, the ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
0
20
0
5
Order By: Relevance
“…The beginning of the "Anthropocene" is reflected by changes in global landscape patterns and ecological functions [3] and this new period is related to the multi-directional evolution of the ecological environment and has generated many ecological risks. The assessment and prevention of ecological risk has become a popular research topic in geography and ecology in response to the comprehensive management of social ecosystems [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The beginning of the "Anthropocene" is reflected by changes in global landscape patterns and ecological functions [3] and this new period is related to the multi-directional evolution of the ecological environment and has generated many ecological risks. The assessment and prevention of ecological risk has become a popular research topic in geography and ecology in response to the comprehensive management of social ecosystems [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, when the economic development level of a region is low, the differences in CES in various scenarios are smaller. Other studies found that when people face more survival risks, their perception of the surrounding CES will be reduced [57]. People's direct experience plays an important role in shaping their perception of the surrounding CES [58].…”
Section: Future Development Managementmentioning
confidence: 98%
“…lead to destabilization and trigger gravitational mass movement (soil, rock, or debris). As a basic geomorphic indicator, elevation and slope were mostly used to estimate erosion, surface runoff, and landscape [27,39,40]. The infiltration of rainwater increased the soil saturation, sharply dropping absorption and causing a substantial decline in shear strength.…”
Section: Criteria Layers In Ecological Risk Assessment (1) Hazards Inmentioning
confidence: 99%
“…Vegetation and water flow were the factors with the greatest effect on soil erosion and slope stability. Vegetation enhances the soil shear strength via a series of mechanical and hydrological effects [27,39,41], and NDVI, which indicates the land surface vegetation cover, has been widely used as an influencing factor when quantifying the probability of geodisasters [41][42][43]. Distance to a river reflects the influence of water flow using simplified representation space from major rivers.…”
Section: Criteria Layers In Ecological Risk Assessment (1) Hazards Inmentioning
confidence: 99%
See 1 more Smart Citation